**Weegy:** b(a + b) - a(a - b) = ab + b^2 - a^2 + ab = -a^2 + 2ab + b^2

**User:**
Find the product.
-2x(x^2 - 3)
-2x3 - 6x
-2x3 + 6x
-2x2 + 6x
6x3

**Weegy:** -2x(x^2 - 3) = -2x^3 + 6x

**User:**
Find the product.
(6a + b)2
12a2 + ab + b2
36a2 + ab + 36b2
36a2 + 12ab + b2
36a2 + b2

**Weegy:** (6a + b)^2 = 6a*6a + 2*6a*b + b*b = 36a^2 + 12ab + b^2

**User:**
Find the product.
(-d + 4)(-d - 4)
-d2 - 16
d2 - 16
d2 + 16
d2 - 8d - 16

**Weegy:** (-d + 4)(-d - 4) = d^2 + 4d - 4d - 16 = d^2 - 16

**User:**
Multiply (6z 2 - 4z + 1)(8 - 3z).
18z3 - 60z2 + 35z - 8
48z2 - 18z + 8
6z2 - 7z + 9
-18z3 + 60z2 - 35z + 8

(More)